Microfinance Institutions and Poverty Reduction: A Cross Regional Analysis (The Pakistan Development Review, 2015)
The alleviation of poverty is one of the most debated issues among the academicians and policy makers. From 1950s to 1980s the poverty reduction program has been based on increase the participation of poor into the economy by better macroeconomic performance. Though the poor part of population mostly engaged in informal sector1 is identified by researchers but has not become the part of economic models and government policy [Robinson (2001)]. Poverty reduction has been institutionalised in 1944 when World Bank was set up. The World Bank worked through governments and institutions by giving loans to developing countries called structural-adjustment programmes. These programmes were highly unsuccessful, created dependence on aid with little help to poor part of societies [Murduch (1999) and Diop, et al. (2007)].